Psychometric assessment of HIV stigma in patients attending a tertiary facility: An initial validation of the Berger HIV stigma scale in a Ghanaian perspective - Thomford, N.E.; Dampson, F.N.; Kyei, G.B. (PLOS ONE, 2023)
Background HIV-related stigma and discrimination are major challenges to people living with HIV (PLWHIV) and are due to misconceptions. Due to socioeconomic variations, there is increased stigma experienced by PLWHIV in sub-Saharan Africa (SSA). Stigma affects adherence to antiretroviral medications by PLWHIV and defeats the goal of achieving viral suppression. This study evaluated the Bergers HIV stigma scale in PLWHIV in Ghana regarding construct validity and reliability and assessed which aspect of stigma is critical for immediate redress. Methods The Berger et al. HIV stigma scale (39 items) and some selected questions from HIV stigma and discrimination measurement tool of the International Centre for Research on Women, Washington, DC were administered to a cohort of PLWHIV in Ghana (n = 160). Clinicodemographic data was collected from their folders and verbally. The psychometric assessment included exploratory factor analysis whiles scale reliability was evaluated as internal consistency by calculating Cronbach’s α. Results The exploratory factor analysis suggested a four-factor solution which is like the original Ber ger HIV scale with sub-scales personalised stigma, disclosure concerns, negative selfimage, and concerns with public attitudes. Items in the sub-scales personalised stigma (15-items), disclosure concerns (6), negative self-image (7) and concerns with public attitudes (6) were reduced compared to the original scale. Cronbach’s α for the overall HIV stigma scale (34-items) was 0.808 whiles the sub-scales α ranged from 0.77 to 0.89. Analysis sug gested the prevalence of a fundamental one-dimensional factor solution which yielded a 34- item scale after removing items for low factor loadings. Disclosure concerns was the highest ranked subscale although our study also found that about 65% of PLWHIV among our study participants had disclosed their status. Conclusion Our 34-item abridged Berger HIV stigma scale showed sufficient reliability with high Cron bach’s α and construct validity. Disclosure concerns ranked high among the sub-scales on the scale. Exploring specific interventions and strategies to address stigma concerns in our population will aid in the reduction of HIV-related stigma and associated consequences.
Research Article